Depression, Post-traumatic Stress Disorder, and Life Satisfaction in Greenlandic Adults - Zaragoza Scherman, Alejandra (Psyke & Logos, 2017)
Suicide is a major public health problem in Greenland. Despite the fact that suicide is highly associated with depression, posttraumatic stress disorder (PTSD), and life satisfaction there are virtually no data about the extent to which Greenlandic individuals experience these mental health problems or a sense of wellbeing. In this study, a group of 137 Greenlandic adults completed measures of depression, PTSD, and life satisfaction. In addition, they also provided memories of traumatic or stressful and positive life events they had experienced during their lives. No sex differences were found in any of the measures. Results showed that 25.8 % of the participants reported symptoms of mild or major depression, while 13% reported high PTSD scores, and 10% of the sample reported being dissatisfied with their lives. Keywords: depression, PTSD, life satisfaction, Greenlandic middle-aged and older adults, life events